Scaling Up the Health Workforce in the Public Sector : The Role of Government Fiscal Policy - Vujicic, M. (2012)
Health workers play a key role in increasing access to health care services. Global and country-level estimates show that staffing in many developing countries - particularly in Sub-Saharan Africa - is far leaner than needed to deliver essential health services to the population. One factor that can limit scaling up the health workforce in developing countries is the government's overall wage policy which sometimes creates restrictions on hiring in the health sector. But while there is considerable debate, the information base in this important area has been quite limited. This paper summarizes the process that determines the budget for health wages in the public sector, how it is linked to overall wage policies, and how this affects staffing in the health sector. The author draws mainly from a recent World Bank report.